Pesquisa de leishmania spp. Em secreção ocular de Felinos domésticos no estado do Tocantins - Rodrigues, Anna karollyne Martins (2024)
Leishmaniasis is a world-famous zoonosis of major public health importance. In Brazil, the northern region is considered endemic for this zoonosis, as evidenced by the high number of affected dogs throughout the state of Tocantins and surrounding states. Felines can be carriers of the disease and remain clinically healthy or still show some non-specific symptoms. Diagnostic techniques with less invasive material collection, minimizing patient stress, facilitate animal handling and reduce alterations in physiological parameters. In this sense, the ocular secretion swab is a possibility to be studied. Cytology is highly specific, practical and inexpensive for diagnosing leishmaniasis. PCR, on the other hand, can be carried out when the cytology is negative, and the animal shows clinical signs or to detect the parasite in asymptomatic patients. In view of this, the aim of this study was to detect the presence of Leishmania spp. by means of cytological analysis and PCR in ocular secretion samples from domestic cats in the state of Tocantins. A total of 46 domestic cats were used, regardless of sex, breed or age, domiciled, stray or sheltered, two of which were known to be positive for leishmaniasis. Two samples of ocular secretion were collected from each animal, one of which was used for cytological evaluation and the other for PCR in search of the protozoa. The two animals known to be positive were positive in cytology and PCR, and the others were negative. The ocular secretion swab sample, which is less invasive, can be used in the analysis for the diagnosis of Leishmania spp. in cats, but further studies are needed to prove this.